Prevalence of occupational health problems and safety measures among workers of Udaypur cement factory limited, Jaljale, Udaypur. - Chaudhary, Indrasen (2012)
ABSTRACT: Occupational health and safety is a cross-disciplinary area concerned with protecting the safety, health and welfare of people engaged in work or employment. The main objective of the study was to find out the prevalence of occupational health problems and safety measures among the workers of the cement factory. This research was carried out in Udayapur Cement factory Ltd. Jaljale of Udaypur District. This research employed descriptive study method and used random sampling for collecting data. The data was collected from administered questionnaire and interview schedule and the respondents were the workers of Udaypur cement factory Ltd., 154 numbers of 30 % of the workers were selected for data collection. The questionnaire was the major tool for data collection. The study found that most of the respondents were males (98.7%) and remaining respondents were females (13%). According to age group highest proportion of the respondents belongs to age group of 40-50 years (58-44%) and most of them were literate (87.6%) and remaining 12.3 percent were illiterate. More than 62.34 percent of the respondents reported that working environment in Udaypur Cement was more noisy and majority of the respondents (74.67%) had reported a kind of stress and hearing problems. There were 46.1 percent respondents reported that they were suffered from various allergies and 53.25 percent were injury at working place. Most of the respondents using gloves (87.66%) for safety. Overall most of the respondents seem to be suffering from the noisy environment, various allergies of the industry and they were found to be unsatisfied of these problems. At last the Government industries workers could get the maximum facilities even in salary. But management committee was careless of their work. These kinds of decrease in facilities may degrade the working opinion of the workers and hence, it should be timely addressed by the company.